Mineralization of phenanthrene by a Mycobacterium sp. - Guerin, W F (1988)
A Mycobacterium sp., designated strain BG1, able to utilize the polycyclic aromatic hydrocarbon phenanthrene as the sole carbon and energy source was isolated from estuarine sediment following enrichment with the hydrocarbon. Unlike other phenanthrene degraders, this bacterium degraded phenanthrene via 1-hydroxy-2-naphthoic acid without accumulating this or other aromatic intermediates, as shown by high-performance liquid chromatography. Degradation proceeded via meta cleavage of protocatechuic acid. Different nonionic surfactants (Tween compounds) solubilized the phenanthrene to different degrees and enhanced phenanthrene utilization. The order of enhancement, however, did not correlate perfectly with increased solubility, suggesting physiological as well as physicochemical effects of the surfactants. Plasmids of approximately 21, 58, and 77 megadaltons were detected in cells grown with phenanthrene but not in those which, after growth on nutrient media, lost the phenanthrene-degrading phenotype. Given that plasmid-mediated degradations of aromatic hydrocarbons generally occur via meta cleavages, it is of interest that the addition of pyruvate, a product of meta cleavage, supported rapid mineralization of phenanthrene in broth culture; succinate, a product of ortho cleavage, supported growth but completely repressed the utilization of phenanthrene. The involvement of plasmids may have given rise to the unusual degradation pattern that was observed.